Pancharatnam–Berry‐Phase‐Based Plasmonic Metasurfaces Enable Wavelength‐Selective Directional Focusing and Vortex - Heyi Zhang; Chunhui Zhu; Zhengyong Song (Advanced Photonics Research)
Multifoci focusing has always been a problem that researchers continue to pay attention to and urgently needs to be solved. Metasurfaces display unprecedented capabilities and flexibilities to solve this problem. In this work, Pancharatnam–Berry (PB)‐phase‐based plasmonic metasurfaces are presented to realize wavelength‐selective directional focusing on the same focal plane. Ultrathin meta‐atoms with the half‐wave plate effect have only three layers, and 360° phase modulation is obtained by axially rotating gold strip based on PB phase. Two metasurfaces are designed to verify our strategy. Above all, a wavelength‐selective directional focusing metasurface is presented to converge right‐handed circularly polarized wave with wavelengths of 187, 271, and 355 μm at different predetermined positions at 810 μm. Next, the second metasurface exhibits the function that three vortex beams carrying orbital angular momentums with different topological charges can be produced under the irradiation of incident wave at the aforementioned wavelengths. In this research, a solid step is paved toward practical applications of flat photonics.